Kondisi Fisik Atlit Shoto-kai Pemerintah Riau - yuga, Gde Ananta Yuga Mediarta (Jurnal Inovasi Olahraga, 2023)
After all data has been collected and processed, because this type of research is descriptive, the analytical technique that can be used is to use frequency distribution techniques (descriptive statistics) with percentage calculations, as explained by Arikunto, (1990), "If a study aims to get a picture or find something as it is about an object under study, then the data analysis technique is used simply by calculating the percentage as the formula used to calculate the percentage is as follows: P = x 100% (Soejono, 1991: 40) Information: P = Percentage F = Frequency of athletes N = Number of karate athletes who take the test (sample)